Global development of artificial intelligence in cancer field: a bibliometric analysis range from 1983 to 2022 - Wang, Sui-Han; Chen, Guoqiao; Zhong, Xin; Lin, Tianyu; Shen, Yan; Fan, Xiaoxiao; Cao, Liping (Frontiers in Oncology, 2023)
Background: Artificial intelligence (AI) is widely applied in cancer field nowadays.The aim of this study is to explore the hotspots and trends of AI in cancer research.The retrieval term includes four topic words ("tumor", "cancer", "carcinoma" and "artificial intelligence") were searched in the database of Web of Science from Jan.1983 to Dec. 2022. Then we documented and processed all data, including the country, continent, Journal Impact Factor and so on using the bibliometric software.Results: A total of 6920 papers were collected and analyzed. We presented the annual publications and citations, most productive countries/regions, most influential scholars, the collaborations of journals and institutions and research focus and hotspots in AI-based cancer research.This study systematically summarizes the current research overview of AI in cancer research so as to lay the foundation for future research.